Species Authentication of Dog, Cat, and Tiger Using Cytochrome β Gene - . Irine; H Nuraini; C Sumantri (Media Peternakan, 2013)
Adulteration of animal food products for economic reason has happened during the last decades. Species identification method development was needed to prevent falsification information. The objective of this research was to study species authentication (dog, cat, and tiger) to ensure animal origin in products using cyt β gene specific marker. DNA extraction and fragment amplification were conducted using phenol-chloroform and multiplex PCR (Polymerase Chain Reaction) method, respectively. This research showed that fragment length of amplification for species tested (dog, cat, and tiger) were 523, 331, 319 bp, respectively. Species specificity was also indicated by high reverse primers homology percentage. Multiplex PCR technique succeed to amplify DNA fragment from species tested, but has a limitation to amplify total DNA composite of mix DNA.